The Influence of the Application of the Cooperative Integrated Reading and Composition (CIRC) Model Assisted by Digital Comic Media on Students' Understanding Reading Abilities - Fasha Putri Audina; Yayan Nurbayan; Indah Nurmahanani (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Reading comprehension is a process of acquiring meaning that actively involves the knowledge and experience that the reader already has and is connected to the content of the reading. Good reading comprehension is very important to achieve reading goals. Low interest in reading is the background to this research. Low reading levels have an impact on students' difficulties in understanding reading. This research aims to determine students' reading comprehension abilities before and after implementing the cooperative integrated reading and composition model assisted by digital comic media as well as the influence of the cooperative integrated reading and composition model assisted by digital comic media on students' reading comprehension abilities. This research uses quantitative research methods with pre-experimental research type one group pretest and posttest. The sample used in this research was class V students in SDN 1 Nagrikaler Purwakarta Regency, totaling 24 students. Based on the research results, it can be concluded that the average score of the pretest results for students' reading comprehension abilities before being given digital action is 66,8 and the average score for students' reading comprehension ability after being given the action is 80. This shows an increase in students’ reading comprehension ability before and after implementing the cooperative integrated reading and composition model assisted by digital comic media. Apart from that, there is an influence of the cooperative integrated reading and composition model assisted by digital comic media on students' reading comprehension abilities.